Evaluation of hybrid PET/CT gastrography in gastric cancer - Jeong, J.; Cho, I.; Kong, E.; Chun, K.; Jang, B.; Kim, T.; Kim, S.; Song, S. (Nuklearmedizin - NuclearMedicine, 2013)
Aim: With the recent advances in multidetector-row CT, a fusion of functional PET with three dimensional (3D) CT gastrography may provide enhanced diagnostic capability and help surgeons during preoperative planning. The diagnostic value of hybrid PET/CT gastrography was compared with that of conventional PET/CT alone in gastric cancer staging. Patients, methods: Patients with gastric cancer (n = 101) confirmed by endoscopic biopsy specimens underwent conventional PET/CT and regional PET with contrast enhanced CT, followed by gastrectomy with lymphadenectomy at our institution from November 2007 to November 2008. These images were fused into a hybrid PET/CT gastrography using the cardiac IQ fusion software. Conventional PET/CT and hybrid PET/ CT gastrography were evaluated for staging of gastric cancer. After gastrectomy, these were compared with pathologic reports respectively. Results: Gastric cancer was diagnosed as 50 early gastric cancer (EGC) and 51 advanced gastric cancer (AGC) on pathologic examination. In EGC, hybrid PET/CT gastrography and PET/CT identified 36 (72%) and 7 (14%) tumours, respectively. Hybrid PET/CT gastrography correctly delineated the subtype of 25 EGC. In AGC, all 51 (100%) tumours were identified on the hybrid PET/CT gastrography compared to 39 (76.5%) tumours on PET/CT. Hybrid PET/CT gastrography correctly classified the morphology of 42 AGC using the Bormann classification. Additionally, depth of invasion was correctly presented in 38 of 51 AGC. Hybrid PET/CT gastrography for regional lymph node (LN) metastasis in the EGC and AGC showed the sensitivity of 75% and 83.9%, and specificity 90.5% and 55%, respectively. Conclusion: Hybrid PET/CT gastrography is the more intuitive and comprehensive method for the preoperative evaluation of gastric cancer than conventional PET/CT.
Keywords: Stomach neoplasm; positron-emission tomography; computed tomo graphic gastrography; multidetector computed tomography